Accounting Profession in Iraq in light of Industry 4.0: Challenges and Benefits - Alkoutaini, Hasan; Ramadhan, Sherzad; Mamoun Walid, Aridah; Ahmed, Fareeba; Khorsheed, Hariwan; Aldulaimi, Amar (Journal of Economic Development, Environment and People, 2024)
This study explores the challenges and advantages of adopting Industry 4.0 technology in Iraq’s accounting profession. The research used questionnaires to gather data from accountants in various industries. The findings suggest that Iraqi accountants are not adequately prepared for Industry 4.0. The study identifies key challenges including digital integration, technical difficulties, lack of skills, cybersecurity concerns, limited budgets, and regulatory constraints. However, there are also potential benefits such as improved efficiency, expanded services, accurate reporting, real-time data analysis, collaboration, increased accessibility, and simplified auditing